Diseases of ageing in Ghana - Ayernor, P.K. (Ghana medical journal, 2012)
The objective of the paper was to outline the chronic non-communicable disease burden of older adults and predict the odds of living with a chronic non-communicable disease in Ghana. The paper utilized descriptive and analytical statistical methods to assess the level of chronic noncommunicable diseases among older adults. Data from the Study on Global Ageing and Adult Health (SAGE) conducted in 2005 in Ghana were used. It comprises 507 individuals aged 50 years and over across the country. The result shows that 45% had oral health problems, 33% were hypertensive, 14% reported having arthritis; 7% had been diagnosed with diabetes, 6% had a cardiovascular condition (Angina) and 4.9% were receiving treatment for stroke or had been diagnosed with stroke. The odds ratio of having a chronic non-communicable condition for those who lived in a rural area was twice as likely as those who reside in an urban area. Chronic non-communicable disease will have significant health and economic implications for the individual, family and the country. The paper posits that the prevalence of chronic non-communicable diseases among the elderly in the country will increase.
Keywords: Ageing population; Older adults; chronic non-communicable diseases; Rural-urban differences; Ghana